2023
DOI: 10.1002/kjm2.12740
|View full text |Cite
|
Sign up to set email alerts
|

Dioscin ameliorates doxorubicin‐induced heart failure via inhibiting autophagy and apoptosis by controlling the PDK1‐mediated Akt/mTOR signaling pathway

Ling Yuan,
Hai‐Gang Ji,
Xiao‐Jing Yan
et al.

Abstract: Heart failure (HF) is a disease with high mortality and morbidity rate. Autophagy is critically implicated in HF progression. The current research was designed to investigate the function of Dioscin on oxidative stress, autophagy, and apoptosis in HF. In this study, doxorubicin (Dox) was employed to induce HF model and HL‐1 cell damage model. Echocardiography implied that Dioscin could dramatically relieve heart function in vivo. Western blotting determined that Dioscin treatment reversed the promotive effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…PIP3 binds to Akt/protein kinase B and phosphoinositide-dependent kinase-1 (PDK1). PDK1 then phosphorylates AKT, which in turn phosphorylates mTOR to inhibit autophagy [24]. Mammalian target of rapamycin complex 1 (mTORC1) signaling negatively regulates the activity of the unc-51-like autophagy-activating kinase (ULK)1 complex [25] (Figure 2).…”
Section: Pi3k/akt/mtor Signaling In Autophagy Regulationmentioning
confidence: 99%
“…PIP3 binds to Akt/protein kinase B and phosphoinositide-dependent kinase-1 (PDK1). PDK1 then phosphorylates AKT, which in turn phosphorylates mTOR to inhibit autophagy [24]. Mammalian target of rapamycin complex 1 (mTORC1) signaling negatively regulates the activity of the unc-51-like autophagy-activating kinase (ULK)1 complex [25] (Figure 2).…”
Section: Pi3k/akt/mtor Signaling In Autophagy Regulationmentioning
confidence: 99%
“…This protective mechanism is associated with the modulation of miR-140-5p-mediated myocardial oxidative stress under the initiation of the Nrf2/sirtuin 2 pathway [20]. Additionally, Yuan et al reported that dioscin modulates the phosphoinositide-dependent protein kinase-1 (PDK1)-regulated Akt/mammalian target of rapamycin (mTOR) pathway to improve DOX-induced heart failure (intraperitoneal injection of 2.5 mg/kg DOX six times in 2 weeks) [21]. These results provide evidence that the therapeutic effect of dioscin on acute DIC may be related to Nrf2-associated oxidative stress.…”
Section: Introductionmentioning
confidence: 99%